Algebra and Trigonometry 10th Edition

Published by Cengage Learning
ISBN 10: 9781337271172
ISBN 13: 978-1-33727-117-2

Chapter 1 - 1.4 - Quadratic Equations and Applications - 1.4 Exercises - Page 110: 34


{-1, 3}

Work Step by Step

$x^2-2x-3 = x^2+x - 3x -3 = x(x+1)-3(x+1)=(x-3)(x+1)=0$ Either x-3=0 that gives x=3 or x+1=0 that gives x=-1
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.